Reaching a socio-ecological tipping point: Overgrazing on the Greek island of Samothraki and the role of European agricultural policies. (July 2018) - Fetzel, Tamara; Petridis, Panos; Noll, Dominik; Singh, Simron Jit; Fischer-Kowalski, Marina
Highlights: Overgrazing on Samothraki has caused soil erosion and a decline in grazing capacity. We present a feed-balance estimate for the period 1970–2012. Our results imply a strong dependency on external feeds since the 1990s. We discuss the role of CAP subsidies and local characteristics as drivers. Abstract: Livestock keeping and food production from grasslands play an important role in the Mediterranean region, where grazing has a long tradition and still is a key livelihood strategy. Yet, in many places widespread degradation (caused by overgrazing) severely threatens the natural resource base and prospects for future food security and sustainable development. On Samothraki, a Greek island, several decades of continuous increase of the local livestock population, exceeding not only the local food base by far but also the local farmers' ability to provide supplementary feed, led to a socio-ecological tipping point turning the dynamics downward. Still, in the face of very restricted marketing opportunities, we find local farmers in an economic deadlock of relying on CAP subsidies as a main source of income and on still too high animal numbers for maintaining an ecological balance of their land while lacking the labor power (due to large-scale migration to Germany in the 1950s and 60 s) to apply adequate management practices. In this paper, we present a feed balance (feed-demand and supply) for sheep and goats from 1970 to 2012 and discuss causes and effects of the excessive growth in animal numbers, as well as reasons for their downturn in the last decade. We describe the island's groundcover and symptoms of soil degradation, and underline our findings by reference to a remote sensing approach. Our findings recently gained in prominence as in September 2017, a state of emergency had to be declared on the island when a major weather event triggered a series of landslides that severely damaged the main town, a number of roads and bridges and even the 700 years old Fonias Tower, a marker of Samothraki tourism.